Creating An Excellent Service Workshop From Customer's Perceptions And Expectations - Kong, Sin Tuck (2006)
This research study analyses and reviews customer perceptions and expectations of service quality as one variable in maintaining competitiveness. It then makes suggestions on the areas car companies can focus on to improve their service and build a more loyal following to remain competitive.